Effect of Feeding Pomegranate (Punica granatum) Peel and Garlic (Allium sativum) on Antioxidant Status and Reproductive Efficiency of Female Rabbits - Omnia Y. Abd-Elfadiel Hagag; Fawzy El-Essawy Younis; Rasha A. Al-Eisa; Eman Fayad; Nahla S. El-Shenawy (Veterinary Sciences, 2023)
Egypt’s animal protein shortfall cannot be overcome by expanding the production of large animals alone, but rather by increasing the production of highly reproducing animals in the livestock unit. The goal of this study was to examine how adding pomegranate peel (PP), garlic powder (GP), or a mixture of the two to the diet of does affect their weight, the number of offspring, reproductive performance, hematological indices, and several antioxidants indicators as well as the liver and kidney functions. A total of 20 adult and mature female mixed rabbits at age 4.5–5 months and averaging 3.05 ± 0.63 kg body weight, were allocated into four experimental groups (n = 5). The first group was provided with the basal diet and was considered as control animals, while the second, third, and fourth groups were fed the basal diet supplemented with PP 3.0%, GP 3.0%, and a mixture of PP 1.5% + GP 1.5%, respectively. After 2 weeks of feeding the experimental diets, natural mating with untreated bucks was carried out. The kits were weighed immediately after parturition, and then every week. The study found that rabbits fed with 3% PP led to a 28.5% increase in the number of kits at birth compared to the control group. As an effect of supplementing PP 3%, GP 3%, and PP 1.5% + GP 1.5%, the birth weight increased by 9.2%, 7.2%, and 10.6%, respectively, as compared to the control. Hemoglobin increased significantly in all treatment groups as compared to the control at the age of kit weaning. Lymph cells increased significantly in the rabbits that were fed with GP (3%) than in other groups and even the control. The results showed that creatinine levels were significantly decreased in the PP (3%) and GP (3%) than in control rabbits. The level of triglycerides significantly declines in groups treated with PP (3%) than in other treatment groups and the control. The addition of PP 3% or GP 3% increased the progesterone hormone. The addition of PP 1.5% + GP 1.5% improved the immunoglobulin IgG. The results of superoxide dismutase, catalase, glutathione, and total antioxidant capacity showed a significant decline in groups treated with GP (3%) than other treated groups. In conclusion, pomegranate is a promising substance to include in a rabbit’s diet, followed by garlic to boost reproductive efficiency.